THE VALUES OF HUMANISM IN CONFUCIANISM - Mir'ah Azizah; Arga Maulana Pasanrangi (Universitas Negeri Makassar, 2022)
Confucianism is the name of one of the schools of Chinese philosophy. The founder of Confucianism was named Confucius. In an age when division, turmoil and constant wars are rampant, Confucius wants to restore the order of heaven (Tianming) so as to unify China and bring peace and prosperity to the people. The humanistic teachings of Confucianism developed into one of the most important things in Chinese civilization. Confucius' most profound teachings lay in his emphasis on self- development or self-civilization, moral example and the ability to make well-trained decisions rather than knowledge of natural laws. His ethics then, is more of a benevolent ethic. The concepts of humanism introduced in Confucianism are: Zhengming (justification, upholding one's name), Yi (virtue), Ren (human kindness), Xiao (respect), Li (ritual), Tianming (sky order). In Chinese terms, Confucianism refers to two meanings: Ju Chiao which refers to religious teachings and Ju Chia which refers to philosophical schools. As Ju Chiao in the religious field the term T'ien or Tian is the main spiritual factor. In the Confucian teachings about Tianming or the orders of the sky, the content is that T'ien gives the power of a country to people he chooses, namely those who are deemed capable of leading a country. Keywords: Humanism, Confucianism, Confucius